Incorporation of CdFe2O4-SiO2 nanoparticles in SbPO4-ZnO-PbO glasses by melt-quenching process - Orives, Juliane Resges [UNESP]; Viali, Wesley R. [UNESP]; Magnani, Marina [UNESP]; Nalin, Marcelo [UNESP] (Ecletica Quimica, 2018)
The development of glasses containing nanoparticles dispersed homogeneously with controlled size and optimum parameters for functionality is a big challenge. In the present work, the ternary system 60SbPO4-30ZnO-10PbO containing CdFe2O4-SiO2 nanoparticles was studied. CdFe2O4 nanoparticles, with average size of 3.9 nm, were synthesized using the coprecipitation method and, in a second step, protected by a silica layer. Different mass percentages of nanoparticles were mixed to the glass precursors and then transformed into glasses by melt-quenching method. Thermal and structural properties were evaluated by differential scanning calorimetry, Raman spectroscopy, scanning electronic microscopy and transmission electron microscopy. While the optical properties were studied by M-Lines spectroscopy and UV-Vis spectroscopy. The glasses obtained were completely transparent, with yellow color and showed no sign of crystallization according to the techniques used. Scanning and transmission electron microscopy confirm that the methodology used for the incorporation of nanoparticles was efficient. The methodology used to protect the nanoparticles prior to incorporate them to glasses, strongly contributes towards the development of new functional glasses useful for magneto-optics devices.
Keywords: Antimony based glass; Cadmium ferrite nanoparticles; Optical properties; Structural properties